Comparison of Anterior and Posterior Approach Bilateral Sacrospinous Ligament Fixation for Vaginal Vault Prolapse - Fatih Şahin; Ramazan Adan (IMR Press, 2023)
Background: We aimed to investigate the outcomes of anterior and posterior approaches in patients who underwent sacrospinous ligament fixation for apical prolapse. Methods: The study included hysterectomized women with grade ≥2 apical prolapse according to the Pelvic Organ Prolapse Quantification (POP-Q) system, who presented to our center between 2019 and 2022. Out of the 48 patients included in the study, 24 underwent posterior bilateral sacrospinous ligament fixation (PB-SSLF), while the other 24 underwent anterior bilateral sacrospinous ligament fixation (AB-SSLF). Postoperative anatomical recurrence of anterior vaginal wall prolapse, according to the POP-Q system, was defined as follows: cystocele ≥ stage II (Aa or Ba ≥-1 cm), recurrent apical prolapse ≥ stage II (C ≥-1 cm), and posterior vaginal wall prolapse ≥ stage II (Ap or Bp ≥-1 cm). Postoperative follow-up visits were scheduled routinely at 1, 3, 6, and 12 months after the operation, and then annually. Complications were recorded according to the Clavien-Dindo classification. Rates in the groups were compared using the Chi-square test. Independent two-group comparisons of numerical variables were performed using the Student t-test when the normal distribution assumption was met and the Mann-Whitney U test when the assumption was not met. The significance level (alpha) was set at p < 0.05. Results: No significant difference was observed in terms of postoperative anterior recurrence between the groups that underwent bilateral anterior and posterior SSLF (16.7% each). Regarding the operation durations, the group that underwent AB-SSLF had longer operation times compared to the group that underwent PB-SSLF (80 minutes and 42.5 minutes, respectively). A higher incidence of postoperative urinary dysfunction was observed in patients who underwent anterior bilateral sacrospinous ligament fixation (p = 0.012). No grade 3b or higher complications were observed according to the Clavien-Dindo classification. Conclusions: AB-SSLF is an effective method in the surgical treatment of apical and anterior pelvic prolapse. However, the anterior compartment failure rate is still a limitation. Further research is required to investigate its long-term efficacy.